A Case of Hyperintense Liver Metastases of Breast Cancer in the Hepatobiliary Phase on Gadoxetic Acid-Enhanced Magnetic Resonance Imaging - Tomoyuki Yamaguchi (Case Reports in Oncology, 2020)
A 64-year-old woman complaining of left arm and breast edema was referred to our hospital. Mammography and ultrasound could not initially show any masses, but magnetic resonance imaging (MRI) showed ill-defined small masses in her left breast. Histological examination showed the tumor to be triple-negative breast cancer. After neoadjuvant chemotherapy, the patient underwent operation. Postoperative histological examination showed massive cancer remnants in the lymph nodes and lymphatics. Enhanced CT taken at the onset of abdominal pain showed multiple liver masses with ring enhancement 17 months after the operation. Gadoxetic acid-enhanced MRI showed hyperintense masses and presumed broad cancer cell permeation to the liver in the hepatobiliary phase. Due to the histologically proven high lymphatic permeability, metastatic sites, and gadoxetic acid-enhanced MRI findings, we judged the liver metastases as lymphatic liver metastases. Due to the marked liver dysfunction at the onset of abdominal pain, the patient received best supportive care and died in 4 months.